(untitled) (PANGEEA, 2025)
ABSTRACT: When natural disasters occur, a huge amount of various types of waste is generated. This post-disaster waste can be a major impediment to emergency life-saving aid and reconstruction. The purpose of this article is to show that after natural disasters the resulting waste can be reused.The experience of previous natural disasters shows that the waste caused by them is often managed in a general way, but still, and that substantial improvements can be made in case of future events. Disaster waste (DW) also presents various opportunities: it can contain valuable materials such as concrete, steel and wood, as well as various organic wastes that can be used for composting. This can be achieved either as a source of income or as materials for reconstructions, thus reducing the use of natural resources from exhaustible sources. Disasters can occur in both developed and developing countries, generating large amounts of disaster waste, including construction and demolition waste (CDW), which must be properly managed like other types of waste.. While developed countries are able to implement appropriate disaster waste management (DWM) strategies to facilitate the recovery processes of various materials, developing countries generally struggle to find the resources and expert ise to develop such strategies and they must be helped. Worldwide, many countries have made various guidelines for the management of these types of waste. Japan, as a disaster-prone country, has suffered from various natural disasters and is always trying to improve DWM.Because of this, Japan can contribute to a proper DWM globally by using these experiences. DWM and general waste management are closely related, where normal waste management is not sufficient, it is very difficult to properly and efficiently manage waste caused by disasters. Improving overall waste management can lead to increased effectiveness of DWM in the event of natural disasters.